2020
DOI: 10.1155/2020/1043251
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Biological Activities of Extracts from Pomelo Peel By-Products under Enzyme and Ultrasound-Assisted Extractions

Abstract: Enzyme-assisted extraction (EAE) and ultrasound-assisted extraction (UAE) were popular methods used to extract bioactive compounds from citrus peels, by-products of fruit processing industry. In this study, the total phenolic content (TPC), total flavonoid content (TFC), naringin and hesperidin contents, and antioxidant and antimicrobial activities of the extracts from pomelo peels using the combined enzyme and ultrasound-assisted extraction (E-UAE) or ultrasound and enzyme-assisted extraction (U-EAE) techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 22 publications
1
31
0
Order By: Relevance
“…However, PFE in the study of Hasan Khan (2018) was not found to induce the inhibitory activity against tested bacteria which could possibly be ascribed to the pomelo variety or maturity stage. Besides, S. typhimurium, and P. aeruginosa were found to be highly susceptible to the treatment that was in agreement with previous reports(Aydeniz Günes ¸er et al, 2018;Tawfik, Al-Haliem, & Al- Ani, 2010;Van Hung, Yen Nhi, Ting, Lan Phi, & Al Loman, 2020).…”
supporting
confidence: 92%
“…However, PFE in the study of Hasan Khan (2018) was not found to induce the inhibitory activity against tested bacteria which could possibly be ascribed to the pomelo variety or maturity stage. Besides, S. typhimurium, and P. aeruginosa were found to be highly susceptible to the treatment that was in agreement with previous reports(Aydeniz Günes ¸er et al, 2018;Tawfik, Al-Haliem, & Al- Ani, 2010;Van Hung, Yen Nhi, Ting, Lan Phi, & Al Loman, 2020).…”
supporting
confidence: 92%
“…Van Hung et al recovered naringenin and hesperidin from pomelo peels using the combined enzyme and ultrasound-assisted extraction. They concluded that the combination of both methods was effective for bioactive compound extraction with the highest antioxidant and antimicrobial activities [ 234 ].…”
Section: Enzymatic Reaction Systemsmentioning
confidence: 99%
“…In the experiment, the antioxidant activity did not correlate with the enzyme concentration. Van Hung et al, [20] reported the antioxidant activity of pomelo peel powder, using enzyme-assisted powder with water extraction over 60 min. It showed a lower DPPH scavenging ability compared with this study at any concentration (28.6% ± 1.1%).…”
Section: Discussionmentioning
confidence: 99%